(untitled) - Underhill, Nic (Cambridge, 1987)
This is a handbook of practical testing techniques intended for anyone who has to design, adapt, or use oral tests of English as a foreign language. It is therefore intended for native- and non-native speaker teachers, testers, course designers, and educational planners. The book follows the logical stages of a test program, beginning with the reasons for testing, an analysis of the learner's background and needs, and the resources available. It goes on to present oral test techniques and variations, with comments on each, and finally discusses scoring techniques, monitoring, and improving a test program. Underhill is concerned exclusively with oral tests in which the learner has to speak out loud. Although it is designed for use in teaching English, the book could readily be used to create tests in other languages
Keywords: Language and languages,Language and languages,Oral communication; Ability testing,Examinations,Examinations